2017
DOI: 10.1371/journal.pone.0176059
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin is a prognostic marker and a potential therapeutic target in breast cancer

Abstract: Ghrelin and obestatin are gastrointestinal peptides, encoded by the same preproghrelin gene. Both are expressed in breast cancer tissue and ghrelin has been implicated in breast cancer tumorigenesis. Despite recent advances in breast cancer management the need for new prognostic markers and potential therapeutic targets in breast cancer remains high. We studied the prognostic impact of ghrelin and obestatin in women with node negative breast cancer.Within a cohort of women with breast cancer with tumor size ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
(47 reference statements)
5
14
0
Order By: Relevance
“…It has recently been recognised that UAG can under some conditions act as a functional ghrelin inhibitor, reducing ghrelin-mediated increases in plasma glucose [22, 26, 28, 72] and lipid [27, 29]. As the ghrelin axis also plays a role in the progression of a number of endocrine-related cancers [5, 3234], including prostate cancer [5, 43], we hypothesised that UAG may have beneficial effects in advanced prostate cancer associated with metabolic syndrome. To evaluate this hypothesis, we examined the effect of UAG on a prostate cancer cell line in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been recognised that UAG can under some conditions act as a functional ghrelin inhibitor, reducing ghrelin-mediated increases in plasma glucose [22, 26, 28, 72] and lipid [27, 29]. As the ghrelin axis also plays a role in the progression of a number of endocrine-related cancers [5, 3234], including prostate cancer [5, 43], we hypothesised that UAG may have beneficial effects in advanced prostate cancer associated with metabolic syndrome. To evaluate this hypothesis, we examined the effect of UAG on a prostate cancer cell line in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This includes prostate cancer, a classical endocrine-related cancer and the most commonly diagnosed cancer in American men after skin cancer [36], where acylghrelin increases cell proliferation and migration [5, 14, 37–46]. UAG also has functional effects in several cancers, including prostate cancer [5, 3234, 43]. In the PC3 prostate cancer cell line, UAG has a biphasic effect, reducing cell proliferation at supraphysiological levels (10nM-1μM) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Complete and/or partial staining with any intensity (>50% IR tumor cells) was designated as positive staining that differs from truly negative staining (< 50% IR tumor cells), background and diffuse non-speci ic staining. The staining of cytoplasmic that can be observed with highpower ields (40X objective) was considered a positive reaction (Grönberg et al, 2017).…”
Section: Scoring Of Immunohistochemical Staining Of Ghrelin Receptormentioning
confidence: 99%
“…It was reported that Ghrelin had a wide variety of physiological functions that range from regulation of food intake, hormonal secretion, insulin secretion modulation, adipogenesis and gastrointestinal motility, and one of the most important orexigenic peptides currently known. The possible role of Ghrelin in tumorigenesis might be contributed to its involvement in proliferation of cells and the stimulation of milk production, together with the its stimulatory effect on Growth hormone levels via Ghrelin axis, in addition to its high levels in females (Chopin et al, 2011;Delporte, 2013;Khatib et al, 2014;Grönberg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation